2018
DOI: 10.1029/2017jb015417
|View full text |Cite
|
Sign up to set email alerts
|

Structural Inheritance Control on Intraplate Present‐Day Deformation: GPS Strain Rate Variations in the Saint Lawrence Valley, Eastern Canada

Abstract: Structural inheritance is one of the key factors commonly proposed to control the localization of strain and seismicity in continental intraplate regions, primarily on the basis of a first‐order spatial correlation between seismicity and inherited tectonic structures. In this paper, we present new GPS (Global Positioning System) velocity and strain rate analyses that provide strong constraints on the magnitude and style of present‐day strain localization associated with the inherited tectonic structures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…Liu and Stein () argue that weakening from rifting is neither necessary nor sufficient for intraplate deformation based on observed seismicity in the NMSZ and north China. Recent quantitative analysis suggests, however, that structural inheritance from past tectonic cycles observed in the Saint Lawrence Valley in eastern Canada is an important factor in driving present‐day intraplate deformation, where the strain rate can be 2 to 11 times higher than the surrounding region (Tarayoun et al, ). This latter study assumes that no other process contributes to observed high deformation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and Stein () argue that weakening from rifting is neither necessary nor sufficient for intraplate deformation based on observed seismicity in the NMSZ and north China. Recent quantitative analysis suggests, however, that structural inheritance from past tectonic cycles observed in the Saint Lawrence Valley in eastern Canada is an important factor in driving present‐day intraplate deformation, where the strain rate can be 2 to 11 times higher than the surrounding region (Tarayoun et al, ). This latter study assumes that no other process contributes to observed high deformation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their sporadic and sparse point density, campaign time series are not amenable to noise model estimation and computation of formal uncertainties. There is no standard method for estimating campaign velocity uncertainty, but most of them rely scaling based on the nearby continuous GNSS sites (Tarayoun et al, 2018;Beavan et al, 2016;Reilinger et al, 2006). In this study, we use synthetic time series constructed from permanent-station parameters (Masson et al, 2019) to 30 generate synthetic campaign time series with the Alps and Pyrenees campaign characteristics (dates and number of surveys).…”
Section: Campaign Datamentioning
confidence: 99%
“…The Global Navigation Satellite System (GNSS) is a primary dataset to study present-day crustal deformation, for example through the computation of strain rate tensors, both in active tectonics areas (e.g., Indonesia or Greece; Gunawan et al,20 2019; Chousianitis et al, 2015) and in very low deformation areas (e.g., Eastern Canada or India; Tarayoun et al, 2018;Banerjee et al, 2008). However, the analysis of regional and local deformation is commonly restricted by several factors, such as the precision of individual GNSS velocities, the presence of non-tectonic transient signals or the methods used to compute strain rates on different spatial scales (e.g., Cardozo et al, 2009;Zhu et al, 2011;Carafa and Bird, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In geodynamic GPS applications, failure to take offsets into account can have major consequences. For example, Thomas et al (2011) estimated velocities of about 2.1 mm yr −1 lower than those of Argus et al (2011), leading to very different interpretations of the data for estimating uplift rates in East Antarctica. Multiple automatic methods exist for offset detection in GPS position time series, but their reliability is limited.…”
Section: Introductionmentioning
confidence: 97%